2019
DOI: 10.1182/bloodadvances.2018023184
|View full text |Cite
|
Sign up to set email alerts
|

NCF1 (p47phox)–deficient chronic granulomatous disease: comprehensive genetic and flow cytometric analysis

Abstract: Mutations in NCF1 (p47phox) cause autosomal recessive chronic granulomatous disease (CGD) with abnormal dihydrorhodamine (DHR) assay and absent p47phox protein. Genetic identification of NCF1 mutations is complicated by adjacent highly conserved (>98%) pseudogenes (NCF1B and NCF1C). NCF1 has GTGT at the start of exon 2, whereas the pseudogenes each delete 1 GT (ΔGT). In p47phox CGD, the most common mutation is ΔGT in NCF1 (c.75_76delGT; p.Tyr26fsX26). Sequence homology between NCF1 and its pseudogenes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
(23 reference statements)
1
9
0
4
Order By: Relevance
“…In addition, we have observed a CD8 + T cell intrinsic role of NOX2 that is essential for autoimmune diabetes initiation (8). Ergo, our data as well as those from other groups support an important role of NOX2 in adaptive immune function in addition to the well-established role of NOX2 in innate immunity (13, 14). The goal of the current study is to elucidate the mechanisms of NOX2 in regulating CD8 + T cell effector function.…”
Section: Introductionsupporting
confidence: 88%
“…In addition, we have observed a CD8 + T cell intrinsic role of NOX2 that is essential for autoimmune diabetes initiation (8). Ergo, our data as well as those from other groups support an important role of NOX2 in adaptive immune function in addition to the well-established role of NOX2 in innate immunity (13, 14). The goal of the current study is to elucidate the mechanisms of NOX2 in regulating CD8 + T cell effector function.…”
Section: Introductionsupporting
confidence: 88%
“…p47 phox CGD accounts for ~25% of all CGD cases in western countries although its frequency rises in regions with high degree of consanguinity [ 13 15 ]. The disease is caused by mutations in the NCF1 gene [ 16 ] (a deletion of GT at the start of the exon 2 accounts for almost 84% of cases [ 17 ]) encoding p47 phox , the cytoplasmic component that, upon phosphorylation and translocation to the membrane, coordinates the assembly of the cytosolic subunits of NADPH oxidase resulting in the activation of the enzymatic complex. p47 phox CGD has been historically associated with a milder phenotype compared with X-CGD as the majority of patients have residual superoxide production; however, infections are still a major cause of mortality and morbidity and patients still suffer from gut disease and inflammation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It proves that the phenomenon of two intact NCF1 genes on one allele (with one of them carrying the c.579G>A mutation) is not restricted to Ashkenazi Jews, but apparently has expanded in this population. Recently, Kuhns et al studied 168 normal individuals in the USA and found 23 of them to have three copies of NCF1 and 4 of them to have four copies of NCF1 genes 16. However, it remains to be proven that this concerns complete NCF1 genes.…”
Section: Discussionmentioning
confidence: 99%